Black carp RIPK1 negatively regulates MAVS-mediated antiviral signaling during the innate immune activation. (August 2020) - Xie, Xinchi; Cao, Yingyi; Dai, Yuhan; Chen, Zhaoyuan; Wei, Jing; Tan, Yaqi; Wu, Hui; Feng, Hao
Abstract: Receptor-interacting serine/threonine protein kinase 1 (RIPK1) is an important regulator of necroptosis and involved in innate immune response in human and mammal; however, its function in teleost fish mains largely unknown. In this paper, the RIPK1 homologue of black carp ( Mylopharyngodon piceus ) has been cloned and characterized to explore its role in immunity. Black carp RIPK1 (bcRIPK1) possesses the similar structure to its mammalian counterpart, which has been identified as a cytosolic protein by immunofluorescence staining. Overexpressed bcRIPK1 in host cells led to the decreased transcription of interferon (IFN) and interferon stimulated genes, and exogenous bcRIPK1 in EPC cells led to the decreased transcription of interferon promoters in reporter assay. Our previous study has identified that black carp MAVS (bcMAVS) functions as an antiviral adaptor protein against both grass carp reovirus (GCRV) and spring viremia of carp virus (SVCV). The reporter assay showed that the IFN-inducing ability of bcMAVS was dampened by bcRIPK1 and the plaque assay demonstrated that the antiviral activity of bcMAVS was inhibited by bcRIPK1. The immunofluorescent staining and co-immunoprecipitation identified the interaction between these two molecules. Thus, the data generated in this paper support the conclusion that bcRIPK1 interacts with bcMAVS and negatively regulates bcMAVS-mediated antiviral signaling. Highlights: bcRIPK1 interacts with bcMAVS. bcRIPK1 suppresses bcMAVS-mediated IFN production. bcRIPK1 suppresses bcMAVS-mediated antiviral activity.